Sars‐Cov‐2 infection as a possible risk factor for prosthesis endocarditis: A challenging redo‐Bentall for subvalvular abscess. Issue 9 (25th June 2022) - Romeo, Maria Grazia; Comentale, Giuseppe; Cirillo, Vera; Pilato, Emanuele
Abstract: Background: Candida Parapsilosis is an unusual agent of prosthetic endocarditis in immunocompetent individuals but Coronavirus disease 2019 is reported to be associated with a transient immunodeficency that exposes patientes to opportunistic infections. Case Report: We describe a dreadful case of Candida Parapsilosis endocarditis in a transient immunosuppressed patient recently infected with severe acute respiratory syndrome‐Coronavirus 2019. Conclusion: Considering that the symptoms of Candida Parapsilosis infection and the symptoms of Coronavirus disease‐2019 may overlap, it is important never to understimate the non‐specific symptoms to improve patient outcome, especially in patient with previous Coronavirurs disease‐2019 infection and with prosthetic material grafting.